Analisis Tingkat Keramahan Lingkungan Alat Tangkap Surface Gillnet di Perairan Gresik - Jamaluddin Jamaluddin; Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
The problems that exist with fishing gear regarding environmental friendliness are becoming more of a concern and priority in marine and fisheries management, such as fishing in Gresik Regency which is carried out using various fishing gear, including the Surface Gillnet. This research was conducted in Gresik Waters in November - December 2024 with the aim of evaluating and determining the level of environmental friendliness of Surface Gillnet fishing gear in Gresik Waters. The method that will be used is a descriptive-qualitative method. This collection comes from respondents, namely fishermen who use surface gillnet fishing gear. The data obtained is in the form of a friendliness level score which includes 9 criteria for environmentally friendly fishing gear based on the Code of Conduct for Responsible Fisheries (CCRF). The result of calculating the environmental friendliness score is 28.93, which means that the Surface Gillnet fishing gear is an environmentally friendly fishing gear.